ASPEK HUKUM PERBUATAN MELAWAN HUKUM TERKAIT EKSEKUSI JAMINAN HAK TANGGUNGAN DALAM KONTRAK KREDIT (Studi Kasus Nomor : 207/Pdt.G/2020/PN Byw) - Frendy Christianto Imanuel Siahaan, (2023)
This research was conducted to explain that credit is so important in economic activity, the Bank is one of the business entities of financial institutions that aims to provide credit and services. In daily practice, credit loans are expressed in the form of written agreements with mortgage guarantees, both underhand and notarized. As a security guarantee, the borrower or debtor will fulfill the obligation. Given the guarantee as one of the elements of lending that can be obtained confidence in the debtor's ability to repay the debt. Debtors who have obtained credit facilities from banks cannot repay their debts. then it will give rise to problem loans which can be said the debtor has defaulted. With the occurrence of problem loans or debts that cannot be repaid by the debtor for a reason so that the bank as the creditor must solve it by executing the guarantee of mortgage rights as stipulated in the law on mortgage rights against credit contract. However, what happened actually led to a lawsuit against the law (PMH). Therefore, the main problem in this research is whether the application of unlawful acts is in accordance with the Act, which is very much contrary to the credit agreement with the guarantee of mortgage rights according to the Mortgage Act.